Determination of Social, Cultural, Personal, dnd Psychological Factors on Purchasing Decisions of SMEs Culiner Products - Lucky Hikmat Maulana (Technium Business and Management, 2023)
The development of the culinary business is growing rapidly, marked by the emergence of more and more varied food vendors. Many SMEs in the culinary business take advantage of practicality in consuming food and drinks. This study aims to determine consumer perceptions and the influence of cultural, social, personal, and psychological factors on purchasing decisions on SMEs products simultaneously or partially. The population and sample are 100 consumers taken by nonprobability sampling technique. The analytical method used in this research is descriptive and verification. The instrument test was carried out with validity and reliability. Research data analysis includes multiple linear regression analysis, multiple correlation analysis, and hypothesis testing. The test results show that cultural, social, personal, and psychological factors simultaneously and partially have a positive and significant effect on purchasing decisions on SMEs culinary products.